如何求解:T(n) = T(n - 1) + n

发布于 2024-08-31 04:49:02 字数 121 浏览 2 评论 0原文

我已经解决了以下问题:

T(n) = T(n - 1) + n = O(n^2)

现在,当我解决这个问题时,我发现界限非常松散。我是否做错了什么,或者只是这样?

I have the following worked out:

T(n) = T(n - 1) + n = O(n^2)

Now when I work this out I find that the bound is very loose. Have I done something wrong or is it just that way?

如果你对这篇内容有疑问,欢迎到本站社区发帖提问 参与讨论,获取更多帮助,或者扫码二维码加入 Web 技术交流群。

扫码二维码加入Web技术交流群

发布评论

需要 登录 才能够评论, 你可以免费 注册 一个本站的账号。

评论(4

风筝有风,海豚有海 2024-09-07 04:49:02

您还需要一个递归关系的基本情况。

T(1) = c
T(n) = T(n-1) + n

为了解决这个问题,您可以首先猜测一个解决方案,然后使用归纳法证明它是有效的。

T(n) = (n + 1) * n / 2 + c - 1

首先是基本情况。当 n = 1 时,这给出了所需的 c。

对于其他 n:

  T(n)
= (n + 1) * n / 2 + c - 1
= ((n - 1) + 2) * n / 2 + c - 1
= ((n - 1) * n / 2) + (2 * n / 2) + c - 1
= (n * (n - 1) / 2) + c - 1) + (2 * n / 2)
= T(n - 1) + n

所以该解决方案有效。

为了首先进行猜测,请注意,当 c 时,您的递归关系会生成三角形数字 = 1:

T(1) = 1:

*

T(2) = 3:

*
**

T(3) = 6:

*
**
***

T(4) = 10:

*
**
***
****

etc..

直观上,三角形大约是正方形的一半,并且在 Big-O 表示法中,可以忽略常数,因此 O(n^2) 是预期结果。

You need also a base case for your recurrence relation.

T(1) = c
T(n) = T(n-1) + n

To solve this, you can first guess a solution and then prove it works using induction.

T(n) = (n + 1) * n / 2 + c - 1

First the base case. When n = 1 this gives c as required.

For other n:

  T(n)
= (n + 1) * n / 2 + c - 1
= ((n - 1) + 2) * n / 2 + c - 1
= ((n - 1) * n / 2) + (2 * n / 2) + c - 1
= (n * (n - 1) / 2) + c - 1) + (2 * n / 2)
= T(n - 1) + n

So the solution works.

To get the guess in the first place, notice that your recurrence relationship generates the triangular numbers when c = 1:

T(1) = 1:

*

T(2) = 3:

*
**

T(3) = 6:

*
**
***

T(4) = 10:

*
**
***
****

etc..

Intuitively a triangle is roughly half of a square, and in Big-O notation the constants can be ignored so O(n^2) is the expected result.

清秋悲枫 2024-09-07 04:49:02

这样想吧:
在递归的每次“迭代”中,您都会执行 O(n) 工作。
每次迭代都有 n-1 项工作要做,直到 n = 基本情况。 (我假设基本情况是 O(n) 工作)
因此,假设基本情况是与 n 无关的常数,则递归迭代次数为 O(n)。
如果每次都有 n 次 O(n) 迭代,则 O(n)*O(n) = O(n^2)。
你的分析是正确的。如果您想了解有关这种解决递归方法的更多信息,请查看递归树。与其他方法相比,它们非常直观。

Think of it this way:
In each "iteration" of the recursion you do O(n) work.
Each iteration has n-1 work to do, until n = base case. (I'm assuming base case is O(n) work)
Therefore, assuming the base case is a constant independant of n, there are O(n) iterations of the recursion.
If you have n iterations of O(n) work each, O(n)*O(n) = O(n^2).
Your analysis is correct. If you'd like more info on this way of solving recursions, look into Recursion Trees. They are very intuitive compared to the other methods.

绾颜 2024-09-07 04:49:02

对于这个问题来说,解决方案非常简单。您必须展开递归:

T(n) = T(n-1) + n = T(n-2) + (n - 1) + n = 
= T(n-3) + (n-2) + (n-1) + n = ... =
= T(0) + 1 + 2 + ... + (n-1) + n 

这里有算术级数,总和为 1/2*n*(n-1)。从技术上讲,您在这里缺少边界条件,但对于任何恒定的边界条件,您都会看到递归是O(n^2)

The solution is pretty easy for this one. You have to unroll the recursion:

T(n) = T(n-1) + n = T(n-2) + (n - 1) + n = 
= T(n-3) + (n-2) + (n-1) + n = ... =
= T(0) + 1 + 2 + ... + (n-1) + n 

You have arithmetic progression here and the sum is 1/2*n*(n-1). Technically you are missing the boundary condition here, but with any constant boundary condition you see that the recursion is O(n^2).

滴情不沾 2024-09-07 04:49:02

看起来差不多正确,但取决于基本情况 T(1)。假设您将执行 n 个步骤来获得 T(n) 到 T(0),并且每次 n 项介于 0 和 n 之间,平均值为 n/2,因此 n * n/2 = (n^2)/2 = O(n^2)。

Looks about right, but will depend on the base case T(1). Assuming you will do n steps to get T(n) to T(0) and each time the n term is anywhere between 0 and n for an average of n/2 so n * n/2 = (n^2)/2 = O(n^2).

~没有更多了~
我们使用 Cookies 和其他技术来定制您的体验包括您的登录状态等。通过阅读我们的 隐私政策 了解更多相关信息。 单击 接受 或继续使用网站,即表示您同意使用 Cookies 和您的相关数据。
原文